Impact of Occupational Safety and Health Practices on Job Satisfaction A Study in Selected Large Scale Apparel Firms in Colombo District - Mihiravi, D.P.; Perera, G.D.N. (Department of Human Resource Management, University of Sri Jayewardenepura, Nugegoda., 2016)
This study attempts to identify the impact of occupational safety and health practices of jumpers on job satisfaction in selected large scale apparel firms in Colombo district. The main aim of this study is to reduce the prevailing empirical gap pertaining to the impact of occupational safety and health practices on job satisfaction among jumpers. Thus, the research problem of this study is what the impact of occupational safety and health practices of jumpers is on job satisfaction among jumpers in selected large scale apparel firms in Colombo district? The data were collected from 86 jumpers in three large apparel firms in Colombo district using simple random sampling method. Primary data collection was through a self-administrated questionnaire consisting of 40 statements with five point Likert scale. The data analyses are used based on the univariate and bivariate methods of SPSS. This study found out that the occupational safety and health practices are positively correlated with job satisfaction of jumpers in selected large scale apparel firms in Colombo district. It is concluded that the occupational safety and health practices are positively correlated with job satisfaction of jumpers in selected large scale apparel firms in Colombo district. All the five dimensions of OSH practices have a positive impact on job satisfactions and indicated statistically significant. Further, it was revealed that there was a high favorable level of job satisfaction and occupational safety and health among the jumpers in the sample.
Keywords: Job Satisfaction; Jumpers; Safety and Health Practices; Large Scale Apparel Firms